COVID-19 and Autoimmunity: A Single Center Prospective Follow-up Study - Sacchi, Maria Cristina; Tamiazzo, Stefania; Bonometti, Ramona; Stobbione, Paolo; Agatea, Lisa; Gaspari, Piera De; Lauritano, Ernesto Cristiano; Maconi, Antonio; Ciriello, Maria Matilde (Archives of Clinical and Biomedical Research, 2021)
Background Various factors, such as viral infections, can act as triggers for the development of autoimmune diseases. In our recent study we reported the presence of autoantibodies in patients diagnosed with COVID-19. To verify whether these autoantibodies persisted over time and led to the development of chronic autoimmune diseases, we conducted a follow-up study at 3 and 6 months after admission. Methods Thirteen of 40 patients enrolled in the previous study gave their consent to the analysis. The same autoimmunity tests performed at the time of diagnosis were carried out in these patients during follow up. Results We showed, compatibly with an acute inflammatory response, that two patients were negative 6 months after diagnosis. In nine patients, autoantibodies were still present at follow-up. Among them, one patient had only ENA positivity. Another patient developed strong positivity for ANA and M2-β and Ku antigens. Currently, the symptoms do not meet full diagnostic criteria for diagnosis of polymyositis, but the patient is closely monitored to check its possible onset. Three patients developed: transient alopecia, autoimmune thrombocytopenia and hearing loss. Other four patients did not show any clinical symptoms. Conclusions In conclusion, our data show that after 6 months, the autoantibodies are still present in the majority of patients. Further investigations will be necessary to check whether these patients will become negative over time or may develop clinical symptoms compatible with the onset of longer-term chronic autoimmune diseases.